Coverage of Funded Pension Plans - Antolin, P (My University, 2008)
This paper presents comparable and standardised data on coverage in voluntary funded pension plans for several OECD countries using household survey data by age, income level, and labour market status for occupational and personal pension plans. The analysis suggests that coverage is unevenly distributed across individuals and there is therefore a need to increase it, at least among the young and the mid-to-low income. The paper ends assessing different policies to increase coverage.
OECD Working Papers on Insurance and Private Pensions, .
Keywords: Ageing; Ageing -- Superannuation usage and finance for aged care; Ageing; Ageing